Analisis Prediksi Kebangkrutan Dengan Metode Altman Z-Score: (Studi Kasus PT. Gudang Garam Tbk) - Nadila Eka Pratiwi; Rhezka Arianti Daulay; Siti Nenti Indriani (CV. ULIL ALBAB CORP, 2022)
The purpose of this study was to determine the potential level of bankruptcy that occurred in the cigarette industry companies listed on the Stock Exchange, namely